(untitled) (Indian Journal of Animal Production and Management, 2025)
Data of 705 Hariana cows, maintained at livestock farm complex, UP Pandit Deen Dayal Upadhyaya Pashu Chikitsa Vigyan Vishwavidyalaya Evam Go Anusandhan Sansthan, DUVASU, Mathura, for a period from 1962 and 2024 was collected to study effect of non-genetic factors on first dry period. The non-genetic factor effects such as period, season and AFC age group were studied by least-squares analysis. The differences between two subclasses of each effect were tested by Duncan Multiple Range Test. Heritability was estimated by paternal half-sib correlation method. First dry period was 306.6 days, with standard error and standard deviation of 7.34 and 193.7 respectively. The overall least-squares mean for first dry period estimated were 297.54 ± 9.60 days. Season and period of calving had significant effect on first dry period. AFC had non-significant effect on first dry period. The heritability estimates for first service period was 0.164. Genetic correlation of first dry period with breeding efficiency (Wilcox method), breeding efficiency (Tomar method) and age at first calving was -0.946, -0.968 and 0.212 respectively.